Effect of Financial Literacy, Investment Risk and Financial Motivation on The Interest of Generation Z to Invest in Sharia Capital Market Islamic Business Perspective - Syafiq, Muhammad Zaky; Habibi, Ahmad; Susanti, Yeni (CV. Civiliza Publishing, 2025)
This study aims to analyze the effect of financial literacy, investment risk and financial motivation on the interest of Generation Z to invest in the Islamic capital market Islamic business perspective. The research methodology used is descriptive quantitative, using the Slovin formula to obtain a population of 100 Generation Z people in Bandar Lampung. Data analysis methods used are data validity test, data reliability test, hypothesis test and coefficient of determination (R2). The results showed that financial literacy has a positive but insignificant effect on the interest of Generation z to invest in the Islamic capital market with a T-statistic value of 1,739 < 1.98 and a p-value of 0.082 > 0.05. Conversely, investment risk variables and also financial motivation have a positive and significant effect on increasing the interest of Generation z to invest with T-statistical values. Investment risk 2,495 > 1.98 and p-value of 0.013 < 0.05 and financial motivation 2,837 > 1.98 and p-value of 0.005 < 0.05.